CRISPR-Cas9 Mediated Knockout of Apoptotic Genes in Human Stem Cells: A Functional Study - Zaman S. Hamza; Tiba Al Temimi; Ghadah Ali Al-Oudah; Kadum A. AlShareffi (Journal of Biomedicine and Biochemistry, 2025)
Gene editing technologies such as have opened new avenues for studying the role of specific genes in cell survival and differentiation. In this study, we employed CRISPR-Cas9 to knock out the pro-apoptotic genes BAX and CASP3 in human induced pluripotent stem cells (hiPSCs). The edited cells were evaluated for viability, proliferation, and differentiation capacity using flow cytometry, qPCR, and lineage-specific markers. Results demonstrated enhanced cell survival under stress conditions and altered differentiation patterns favoring mesodermal lineage. These findings suggest that modulating apoptotic pathways in stem cells can significantly impact regenerative medicine strategies and improve cell-based therapies.